NUCLEAR MAGICS AT MAGNETOROTATIONAL SUPERNOVA EXPLOSION - Kondratyev, V. N.; Korovina, Yu. V.; Mishenina, T. V. (Одеські астрономічні публікації, 2016)
Nucleosynthesis at magnetorotational supernova explosion is considered by employing arguments of nuclear statistical equilibrium. Effects of ultra-strong nuclear magnetization are demonstrated to enhance the portion of titanium product. The relation to an excess of 44Ti revealed from the Integral mission data and galactic chemical evolution is discussed.